Comparative Analysis of Fundamental Physics Laboratory Skills Among First-Semester Students in Physics, Chemistry, and Biology Education Programs - Taufik, Muhammad; Hikmawati, Hikmawati (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2024)
This comparative study evaluates the practical laboratory skills of first-semester students in Physics, Chemistry, and Biology Education programs at PMIPA FKIP Universitas Mataram. The research highlights significant variations in skill acquisition, with students in the Physics group (Fis A) demonstrating notably higher proficiency levels compared to students in the Biology (Bio A) and Chemistry (Kim C) groups. The findings underscore the importance of tailored instructional strategies and curriculum enhancements to optimize laboratory instruction and foster skill development across diverse scientific disciplines. By offering evidence-based insights into the effectiveness of laboratory instruction in physics, chemistry, and biology, this study contributes valuable information to the discourse on science education, providing essential guidance for educators to enhance student outcomes in science education programs at PMIPA FKIP Universitas Mataram.